The knowledge, attitude and behavior related to the tuberculosis and approaches of tuberculosis therapy by the physicians providing first step service - Deveci, S Erhan; Turgut, Teyfik; Açik, Yasemin; Deveci, Figen; Muz, M Hamdi (My University, 2003)
Before a performed education of tuberculosis for physicians who give first step treatment in our city center, a questionnaire was applied to the participants to evaluate the knowledge, attitude, behavior and approach to the treatment. The 66 practicing physician having an employment period of 64.88 +/- 39.42 months were coming from tuberculosis eradication dispensers at the rate of 3%, and from heath center at the rate 97%. The percentage of facing with tuberculosis patients in physicians, exclude who work in tuberculosis eradication dispensers, per year was median 7.30 +/- 9.77 (0-50). 21.2%, of the physicians determine that disease could be spread by only with respiratory tract, 77.3% of them consider that other than respiratory tract and 59.1% of them deemed that the most important factor is living in the same place with a tuberculosis patient and 75.8% of them determine that for a certain diagnosis the sputum examination is enough. 80.3% of the participants said that in our country conditions PPD must be done for the diagnosis. When the most important 4 tuberculosis drugs are asked only 16.7% of the physicians include morphozinamide as a first choice tuberculosis therapy. 48.5% of the physicians deemed that the therapy duration must be at least 6 months. 74.2% of them determine that follow up the disease must be made by sputum plus another examination, 93.9% of them indicated that the tuberculosis patients must be reported to tuberculosis eradication dispensers. When the hepatotoxicity is occurred, only 27.3% of the physicians could interfere the necessary implementation. 74.2% of them determine that the most important problem in control of tuberculosis is about diagnosis, therapy and follow up. When the directly observed treatment short course (DOTS) strategy is asked 16.7% of them gave correct answer. 34.9% of the first step physicians think that tuberculosis eradication dispensers is the primary responsible center in the control of tuberculosis but 53% of them think that tuberculosis eradication dispensers is inadequate in this subject. In conclusion, the first step practice physicians who work in Elazig city center have insufficient knowledge and it is needed periodically postgraduate education.
Birinci Basamak Hekimlerinin Akciger Tüberkülozu Konusunda Bilgi, Tutum ve Davranişlari ile Tedavi Yaklaşimlari.
Keywords: Adult; Antitubercular Agents; Humans; Physician's Practice Patterns; Tuberculosis; Turkey; tuberculostatic agent; adult; article; clinical practice; human; statistics; tuberculosis; Turkey (republic)